The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fimmu.2023.1181688
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of Pseudomonas aeruginosa mannose-sensitive hemagglutinin on inflammation and immune function in percutaneous nephrolithotomy patients with upper urinary tract calculi complicated with infection

Abstract: ObjectiveTo study the effect of an injection of Pseudomonas aeruginosa mannose-sensitive hemagglutinin (PA-MSHA) on inflammation and immune function in patients with upper urinary tract calculi complicated by infection who have undergone percutaneous nephrolithotomy.MethodsWe retrospectively recorded the clinical data of patients with upper urinary tract calculi complicated by infection who have undergone Percutaneous nephrolithotomy(PCNL) in the Department of Urology, 2nd Affiliation Hospital of Kunming Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, research on the correlation between kidney stones, BUN, and NK cells is sparse. A study on urinary tract stones with infection noted changes in NK cells, but the specific mechanisms were not explored ( 72 ). Another study investigating risk factors for death in COVID-19 patients found that elevated urea nitrogen and NK cells correlated with a poor prognosis ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, research on the correlation between kidney stones, BUN, and NK cells is sparse. A study on urinary tract stones with infection noted changes in NK cells, but the specific mechanisms were not explored ( 72 ). Another study investigating risk factors for death in COVID-19 patients found that elevated urea nitrogen and NK cells correlated with a poor prognosis ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and clinical data show that PA-MSHA can stimulate the immune response via the TLR4 signaling pathway and thus prevent the development of sepsis after surgery. PA-MSHA stimulated the release of serum pro-inflammatory mediators (TNF-α, IL-1β, and IL-6) 8 days after the intervention but increased anti-inflammatory mediators (IL-4 and IL-10) after 16 days, balancing the activity of the immune system to prevent infections [23,27]. PA-MSHAs immune-related and anti-tumor characteristics led to its approval in China in 1998 as a complementary cancer treatment that aims to boost patients' immune systems and thus improve the treatment of malignant tumors such as breast, gastric, bladder, hepatocellular, and colorectal [16,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that Pseudomonas aeruginosa is classified as an aerobe, it functions as a facultative anaerobe, capable of producing energy under oxygen-limited conditions by using alternative electron acceptors such as nitrate (NO 3 − ), nitrite (NO 2 − ), and nitrous oxide (N 2 O) [22]. While a live form of Pseudomonas aeruginosa is highly virulent and can cause fatal infections in humans, its inactivated, genetically modified form and its toxin, exotoxin A, have been proposed as potential immune-modulating and cytotoxic anti-tumor agents [23][24][25]. A genetically transformed subtype of Pseudomonas aeruginosa bacteria is called Pseudomonas aeruginosa-mannose-sensitive hemagglutinin (PA-MSHA), a bacteria killed at temperatures above 65 • C. It is a biologically engineered strain coated with fragile and straight MSHA (mannose-sensitive hemagglutination) fimbriae [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation